Going digital: Changing the game of Danish publishing. (1st June 2015) - Hjarvard, Stig; Helles, Rasmus
This article aims to analyse current transformations in the Danish book publishing industry in light of the convergence between the book and the broader media culture. We focus on changing relationships between actors (publishing houses, bookstores, etc.) in the trade book's circuit of production, distribution and consumption. The development of the e-book challenges established routines of publishers, which must cope with new groups of actors in both the production and distribution of their products as well as new ways for readers to access and consume books. Methodologically, the study is based on qualitative interviews with key organizational actors in the Danish publishing industry and document studies of available industry information and statistics. On a theoretical level, the project combines organizational theory and institutional perspectives of mediatization in order to address the question of how the introduction of new media reconfigures old media industries. In particular, we focus on the interplay between book business actors' perceptions of digital technology, the changing market conditions, and the possibilities this entails for them.The convergence between the book and other media is enabled by 'institutional entrepreneurs', who import perceptions and practices from other media industries into book publishing. These changes at the organizational level also affect the balance between 'market' and 'cathedral' in the book publishing industry as a whole. The distinction between 'brownfield' and 'greenfield' development allows us to understand why existing players in the book market generally try to adapt to digital technologies in ways that do not put their existing businesses at risk, while newcomers may face fewer barriers to pursuing new technological opportunities.